2009
DOI: 10.1093/bja/aep198
|View full text |Cite
|
Sign up to set email alerts
|

Time delay of electroencephalogram index calculation: analysis of cerebral state, bispectral, and Narcotrend indices using perioperatively recorded electroencephalographic signals

Abstract: Our results may show a limitation of the value of electronic EEG indices in prevention of awareness with recall. Furthermore, due to different time delays for ascending and descending values, the results of pharmacodynamic studies may be influenced by this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 21 publications
2
66
1
Order By: Relevance
“…When there is a change in a patient's state (e.g., from unresponsive to awake), changes are apparent in the raw EEG trace about a minute before they are reflected in processed EEG indices like the BIS. 102 As with all monitoring techniques, the use of processed or raw EEG during cardiac surgery presents both advantages and disadvantages ( Table 4). The effectiveness of BIS monitoring in preventing intraoperative awareness with postoperative explicit recall remains controversial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When there is a change in a patient's state (e.g., from unresponsive to awake), changes are apparent in the raw EEG trace about a minute before they are reflected in processed EEG indices like the BIS. 102 As with all monitoring techniques, the use of processed or raw EEG during cardiac surgery presents both advantages and disadvantages ( Table 4). The effectiveness of BIS monitoring in preventing intraoperative awareness with postoperative explicit recall remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…101,102 The time taken for the index to reflect the state change varies from 30 seconds to two minutes. This means that the value displayed by the BIS might reflect the patient's state of arousal a minute in the past, rather than their current state.…”
Section: Delay In Responsementioning
confidence: 99%
“…These include influence of electromyographic (EMG) activity [5,14,18], electrical or mechanical artifacts from medical devices [23,38,81], time delay [113], specific clinical conditions such as hypovolaemia, hypotension, cerebral ischaemia, hypoglycaemia and hypothermia [23], inter-individual variability of baseline EEG characteristics [68,111] and types of drugs [44]. In addition, opioids may interfere with the EEG-signal during administration of the hypnotic agent [26,50,63,67,84,88] thus rendering the reliability of indices during multidrug administration questionable.…”
Section: Controlled Variablesmentioning
confidence: 99%
“…Using perioperatively recorded EEG data from their database, Zanner et al [99] found time delays for all indices between 24 and 122 s before the new state was indicated. They conclude that due to different time delays for ascending and descending values, the results of pharmacodynamic studies may be influenced by this phenomenon.…”
Section: Pharmacodynamic Modellingmentioning
confidence: 99%